2016
DOI: 10.1177/1479972316643699
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exercise modality and intensity on energy expenditure and cardiorespiratory response in adults with obesity and treated obstructive sleep apnoea

Abstract: To inform recommendations for the exercise component of a healthy lifestyle intervention for adults with obesity and treated obstructive sleep apnoea (OSA), we investigated the total energy expenditure (EE) and cardiorespiratory response to weight-supported (cycling) and unsupported (walking) exercise. Individuals with treated OSA and a body mass index (BMI) > 30 kg/m 2 performed an incremental cardiopulmonary exercise test on a cycle ergometer and a treadmill to determine the peak oxygen uptake ðVO 2pk Þ. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Interestingly, the present meta-analysis revealed that aerobic exercise, but not other exercise modalities, lead to significant increase in adiponectin levels and a reduction in leptin levels. This was also found in previous meta-analyses [64,65], and might be explained through greater negative energy balance induced by aerobic exercise as compared to other exercise modalities [74], but also an overall greater effect of aerobic exercise on body weight and fat mass [75].…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, the present meta-analysis revealed that aerobic exercise, but not other exercise modalities, lead to significant increase in adiponectin levels and a reduction in leptin levels. This was also found in previous meta-analyses [64,65], and might be explained through greater negative energy balance induced by aerobic exercise as compared to other exercise modalities [74], but also an overall greater effect of aerobic exercise on body weight and fat mass [75].…”
Section: Discussionsupporting
confidence: 79%
“…In our study, however, no changes in ADIPO concentration were observed in any of the analyzed groups. The authors suggest that significant changes in the concentration of ADIPO are influenced by a higher negative energy balance caused by aerobic exercise compared to other types of activity [57]. There are also reports in which the interventions did not have a significant effect on the concentration of ADIPO.…”
Section: Discussionmentioning
confidence: 95%
“…In a direct comparison of weight supported and unsupported (cycling versus treadmill walking) exercise at 60% and 80% VO 2 peak, treadmill walking was associated with the greatest energy expenditure and with a higher cardiovascular stimulus in obese individuals. 60 However, whether this translates to a more effective training regime with the additional factors of comfort, tolerance and compliance remains unknown.…”
Section: Metabolic Syndrome and Copdmentioning
confidence: 99%
“… 62 Furthermore, the relationship between the progression of breathlessness with increasing ventilation is similar between walking and cycling in obese individuals with COPD, 63 whereas in obese individuals without COPD, there is a greater progression of breathlessness with cycling compared to treadmill walking and earlier termination of exercise. 60 …”
Section: Metabolic Syndrome and Copdmentioning
confidence: 99%